Antifungal Properties and Target Evaluation of Three Putative Bacterial Histidine Kinase Inhibitors - Deschenes, Robert J. (American Society for Microbiology, 1999)
Histidine protein kinases have been explored as potential antibacterial drug targets. The recent identification of two-component histidine kinases in fungi has led us to investigate the antifungal properties of three bacterial histidine kinase inhibitors (RWJ-49815, RWJ-49968, and RWJ-61907). All three compounds were found to inhibit growth of the Saccharomyces cerevisiae and Candida albicans strains, with MICs ranging from 1 to 20 μg/ml. However, deletion of SLN1, the only histidine kinase in S. cerevisiae, did not alter drug efficacy. In vitro kinase assays were performed by using the Sln1 histidine kinase purified from bacteria as a fusion protein to glutathione S-transferase. RWJ-49815 and RWJ-49968 inhibited kinase a 50% inhibitory concentration of 10 μM, whereas RWJ-61907 failed to inhibit at concentrations up to 100 μM. Based on these results, we conclude that these compounds have antifungal properties; however, their mode of action appears to be independent of histidine kinase inhibition.